Foot Ball Squad - Frank Aston::::::photographer::: (1909)
Group portrait of football team in uniform, with coach Coleman, all standing, on athletic field; main buildings in background (Published in Polytechnic J. (v.5, no.2, Nov. 1909 and v.5, no. 8, June 1910).